Respuesta :

Answer:

So you have the multiplication and substitution right. It's just the subtraction.

Step-by-step explanation:

Now, the equation was y = 4x - 2

In the first one x = -3

So it will be 4(-3) - 2

Note: Anytime you see a bracket it means multiplication.

4× -3 = -12 and

-12 - 2 = -14

This is because a negative number minus another number is always negative.

And when dealing with negative numbers you add them but you negate the answer.

For example;

The second one will be -8 - 2

And 8 + 2 = 10

But since the numbers are negative we just negate the 10 making it - 10.

I hope this helps